Reduced total hardness of fresh water enhances the efficacy of bathing as a treatment for amoebic gill disease in Atlantic salmon, Salmo salar L - Roberts, SD; Powell, MD (2003)
The current treatment for amoebic gill disease (AGD)-affected Atlantic salmon involves bathing sea-caged fish in fresh water, often sourced from local dams, for 3-4 h. In both a small-scale laboratory and an on-farm field experiment, the effects of water hardness on the efficacy of freshwater bathing were assessed. Results showed that soft fresh water (19.3-37.4 mg L -1 CaCO3), whether it be naturally soft city mains water or artificially softened dam water, was more efficacious at alleviating AGD in affected fish than hard fresh water (173-236.3 mg L-1 CaCO 3). Soft freshwater bathing significantly reduced viable gill amoebae numbers (from 73.9 to 40.9% of total count) and significantly alleviated gill pathology, both gross and histological. Following bathing, gross gill pathological scores of soft freshwater bathed fish lagged 2 weeks behind hard freshwater bathed fish. Significant gill lesion fragmentation, and shedding of lesion-associated hyperplastic tissue, was accompanied by a significant reduction in AGD-affected gill filaments in soft freshwater bathed fish. Furthermore, soft freshwater bathing alleviated the blood plasma electrolyte imbalance seen in control (sea water) and hard freshwater bathed fish. This study showed that the use of soft fresh water for bathing AGD-affected Atlantic salmon could be an improvement to the current method of treatment. Not only does it reduce gill amoeba numbers, but also, it is of a therapeutic advantage with the potential to reduce bathing frequency.